COMPARATIVE EFFICACY OF SACUBITRIL/VALSARTAN VERSUS RENIN–ANGIOTENSIN SYSTEM INHIBITORS IN ADULT HEART FAILURE: A META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS - DAS, PRANAB; DAS, BODHISATYA (International Journal of Current Pharmaceutical Research, 2026)
Objective: To evaluate the comparative effect of sacubitril/valsartan versus angiotensin-converting enzyme inhibitors or angiotensin receptor blockers on all-cause mortality in adults with heart failure using evidence from randomized controlled trials. Methods: A systematic review and meta-analysis of randomized controlled trials was conducted in accordance with PRISMA 2020 guidelines. Electronic databases including PubMed, Scopus, Google Scholar, and the Cochrane Library were searched to identify eligible studies. Trials enrolling adults with heart failure and directly comparing sacubitril/valsartan with an ACE inhibitor or ARB were included. The primary outcome was all-cause mortality. Risk ratios with 95% confidence intervals were pooled using an inverse-variance fixed-effect model. Results: Three randomized controlled trials comprising more than 18,000 participants met the inclusion criteria. Sacubitril/valsartan was associated with a statistically significant reduction in all-cause mortality compared with ACE inhibitors or ARBs (pooled RR = 0.89; 95% CI: 0.83–0.95). Statistical heterogeneity was low (I² = 12.7%). The observed mortality benefit was largely driven by trials enrolling patients with reduced ejection fraction. Conclusion: This meta-analysis demonstrates that sacubitril/valsartan confers a modest but significant reduction in all-cause mortality compared with conventional renin–angiotensin system inhibitors in adults with heart failure. These findings support the preferential use of angiotensin receptor–neprilysin inhibition in appropriate patients, particularly those with reduced ejection fraction, while highlighting the need for further randomized evidence in other heart-failure phenotypes.